2021
DOI: 10.1016/j.cgh.2020.06.071
|View full text |Cite
|
Sign up to set email alerts
|

No Benefit of Concomitant Immunomodulator Therapy on Efficacy of Biologics That Are Not Tumor Necrosis Factor Antagonists in Patients With Inflammatory Bowel Diseases: A Meta-analysis

Abstract: BACKGROUND & AIMS:There is debate over whether patients with inflammatory bowel diseases (IBD) treated with biologics that are not tumor necrosis factor antagonists (such as vedolizumab or ustekinumab) should receive concomitant treatment with immunomodulators. We conducted a meta-analysis to compare the efficacy and safety of concomitant immunomodulator therapy vs vedolizumab or ustekinumab monotherapy. METHODS:In a systematic search of publications, through July 31, 2019, we identified 33 studies (6 randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 52 publications
2
34
2
3
Order By: Relevance
“…However, as discussed above some cohorts have suggested that combination therapy could improve the clinical efficacy of UST ( 24 26 ). Nonetheless, this observation has not been confirmed in more recent cohorts and one meta-analysis ( 56 , 57 ).…”
Section: Predictive Factors Associated To Ustekinumab Responsementioning
confidence: 79%
See 2 more Smart Citations
“…However, as discussed above some cohorts have suggested that combination therapy could improve the clinical efficacy of UST ( 24 26 ). Nonetheless, this observation has not been confirmed in more recent cohorts and one meta-analysis ( 56 , 57 ).…”
Section: Predictive Factors Associated To Ustekinumab Responsementioning
confidence: 79%
“…Whereas, data about the efficacy of combination therapy with TNF antagonists has consistently shown an improvement in clinical and endoscopic outcomes ( 54 , 55 ), evidence with UST or vedolizumab shows controversial results. Up to now, most of the evidence suggests no benefit of combination therapy with immunomodulators ( 56 , 57 ). A recent meta-analysis including 15 studies found no improvement in clinical or endoscopic outcomes between patients receiving monotherapy or a combination of both drugs (OR, 1.1; 95% CI, 0.87–1.38; and OR, 0.58; 95% CI, 0.21–1.16, respectively) ( 57 ).…”
Section: Predictive Factors Associated To Ustekinumab Responsementioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of 31 studies (randomized controlled trial, n = 6; cohort studies, n = 25) of IBD patients treated with UST or VDZ was recently published. In this study, combination therapy was no more effective than monotherapy as induction or maintenance therapy [ 43 ].…”
Section: Combination Therapy and Immunogenicitymentioning
confidence: 99%
“…In our original cohort, there was indeed a difference in concomitant medication use at baseline between vedolizumab and ustekinumab. However, concomitant immunomodulating medication does not have a significant impact on effectiveness outcomes but does come with an increased risk of severe infections 7‐10 . Therefore, we did not add concomitant medication to our multiple logistic regression model for effectiveness outcomes but did use it for the analysis of safety outcomes.…”
mentioning
confidence: 99%